2016
DOI: 10.3892/ol.2016.4075
|View full text |Cite
|
Sign up to set email alerts
|

Metformin: A candidate for the treatment of gynecological tumors based on drug repositioning

Abstract: Abstract. Metformin is a first-line drug used for the treatment of type 2 diabetes. Recently, metformin has been reported to reduce the carcinogenic risk and inhibit tumor cell growth in glioma and breast cancer. The anticancer action of metformin involves the enhancement of phosphorylation of liver kinase B1, activation of adenosine monophosphate-activated protein kinase and inhibition of mammalian target of rapamycin, which reduces cell growth. Metformin is anticipated to exert antitumor effects in gynecolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 74 publications
0
25
0
Order By: Relevance
“…The potential anticancer properties of metformin are thought to be mediated both directly via the 5' adenosine monophosphateactivated protein kinase (AMPK)/mammalian target of rapamycin (mTOR) pathway and indirectly by reducing circulating glucose and insulin levels (7). Recently there has been much interest in the idea of repurposing metformin as a preventive agent and co-treatment for cancer (40), and several clinical studies on metformin and EC are ongoing despite limited scientific data available.…”
Section: Discussionmentioning
confidence: 99%
“…The potential anticancer properties of metformin are thought to be mediated both directly via the 5' adenosine monophosphateactivated protein kinase (AMPK)/mammalian target of rapamycin (mTOR) pathway and indirectly by reducing circulating glucose and insulin levels (7). Recently there has been much interest in the idea of repurposing metformin as a preventive agent and co-treatment for cancer (40), and several clinical studies on metformin and EC are ongoing despite limited scientific data available.…”
Section: Discussionmentioning
confidence: 99%
“…Long-term use (≥ 30 prescriptions) of metformin (and not sulfonylureas or insulin) was associated with a trend towards reduced risk (OR=0.61, 95% CI: 0.30–1.25), but the results were not statistically significant. Additional studies have observed decreased incidence and mortality among metformin treated groups 349 . Given the absence of good screening tests, the potential for use of metformin as a chemopreventive agent merits further exploration.…”
Section: Risk Factors and Preventive Factorsmentioning
confidence: 96%
“…[174][175][176][177] The efficacy of metformin for the treatment of endometrial, cervical, breast, and ovarian cancer has been suggested in preclinical studies and clinical trials. 154 The anticancer mechanisms of metformin have been assessed by its ability to inhibit pro-survival and anti-apoptotic signals mediated by mammalian target of rapamycin complex 1, EGFR, and MAPK. [178][179][180][181] Metformin may target TYRO3 to prevent cell proliferation and reduce chemoresistance.…”
Section: Metforminmentioning
confidence: 99%